2018
DOI: 10.1029/2018jd028799
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mean Wind Variations and Gravity Wave Forcing Via a Meteor Radar Chain and Comparison with HWM‐07 Results

Abstract: We present an analysis of long‐term observation of the mean winds in the mesosphere and lower thermosphere region. The neutral wind data are collected over the period of January 2009 to November 2017 from a chain of meteor radars along the 120°E meridian in the Northern Hemisphere which consists of four stations at Mohe (MH; 53.5°N, 122.3°E), Beijing (BJ; 40.3°N, 116.2°E), Wuhan (WH; 30.5°N, 114.6°E), and Sanya (SY; 18.3°N, 109.6°E). The annual oscillation dominates the neutral wind pattern at midlatitudes whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…For instance, the phase of the maximum shifts from spring (May) to winter (January) across the spring equinox from the high latitudes to the low latitudes in the Northern Hemisphere. Referring to the recent studies by Jia et al (2018) and Ma et al (2018), a similar feature was also present in the zonal mean winds simultaneously observed by the MMR, BMR, McMR and WMR at northern midlatitudes; they reported that the zonal winds above 85 km generally exhibit an annual variation with a maximum during the summer (eastward), and they further demonstrated that the wind shifts (i.e., the zero zonal wind) near the spring equinox. In addition, based on their results, we also find that the phase of the maximum in the zonal wind also shifts as the latitude decreases; meanwhile, the time at which the zonal wind shifts also demonstrates a transition across the spring equinox from the MMR to the WMR, which is similar to the observed mesopause relative densities shown in Fig.…”
Section: Composite Analysis For the Global Mesopause Relative Densitysupporting
confidence: 67%
See 2 more Smart Citations
“…For instance, the phase of the maximum shifts from spring (May) to winter (January) across the spring equinox from the high latitudes to the low latitudes in the Northern Hemisphere. Referring to the recent studies by Jia et al (2018) and Ma et al (2018), a similar feature was also present in the zonal mean winds simultaneously observed by the MMR, BMR, McMR and WMR at northern midlatitudes; they reported that the zonal winds above 85 km generally exhibit an annual variation with a maximum during the summer (eastward), and they further demonstrated that the wind shifts (i.e., the zero zonal wind) near the spring equinox. In addition, based on their results, we also find that the phase of the maximum in the zonal wind also shifts as the latitude decreases; meanwhile, the time at which the zonal wind shifts also demonstrates a transition across the spring equinox from the MMR to the WMR, which is similar to the observed mesopause relative densities shown in Fig.…”
Section: Composite Analysis For the Global Mesopause Relative Densitysupporting
confidence: 67%
“…Figure 11 shows a comparison of the climatology of the mesopause relative density at 90 km in the composite year among the meteor radars in addition to the mesopause relative densities calculated simultaneously by the US Naval Research Laboratory Mass Spectrometer and Incoherent Scatter (NRLMSISE-00) model (Picone et al, 2002) and Whole Atmosphere Community Climate Model version 4 (WACCM4). The WACCM is an atmospheric component of the Community Earth System Model (CESM) version 1.0.4 developed by the National Center for Atmospheric Research; the key features are described in detail in Marsh et al (2013). In addition, the WACCM is a superset of the Community Atmospheric Model version 4 with 66 vertical hybrid levels from the surface to the lower thermosphere (∼ 145 km); the vertical spacing increases with the altitude from ∼ 1.1 km in the troposphere to 1.1-1.8 km in the lower stratosphere and 3.5 km above ∼ 65 km.…”
Section: Composite Analysis For the Global Mesopause Relative Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The daily averaged wind has the maximum values of 74.0 m/s at about 12 km on day 30 in the MST radar measurement and 77.0 m/s at 84 km on day 61 in the meteor radar observation, while the maximum westward wind speed is only 28.5 m/s at 98 km on day 63. The large eastward winds in the troposphere and mesosphere are caused by the tropospheric and mesospheric westerly wind jets in winter, and are in agreement with the horizontal wind model (HWM07) results (Drob et al, ; Ma et al, ).…”
Section: Quasi 30‐day Oscillationsupporting
confidence: 89%
“…Meteor radar operates both day and night under all kinds of weather and geographical conditions and provides good long-term observations; consequently, meteor radar is a 20 powerful technique for studying the dynamics and climate of the mesopause region, including its wind fields and temperatures (e.g., Hocking et al, 2004;Holdsworth et al, 2006;Hall et al, 2006Hall et al, , 2012Stober et al, 2008Stober et al, , 2012Yi et al, 2016;Lee et al, 2016;Holmen et al, 2016;Liu et al, 2017;Lima et al, 2018;Ma et al, 2018). In addition to acquiring wind and temperature measurements, meteor radar has also been 25 applied in recent years to estimate the atmospheric density in the mesopause region.…”
Section: Introductionmentioning
confidence: 99%